2022
DOI: 10.51253/pafmj.v72i5.3619
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco Use and Its Association with Head and Neck Tumors and its relationship with Ethnicity; A Hospital Based Study

Abstract: Objective: To identify smokeless tobacco as a risk factor in the development of head and neck cancers and to assess the role of ethnicity in the use of smokeless tobacco in developing head and neck cancers. Study Design: Case-control study. Place and Duration of Study: Department of Medical Oncology, Jinnah Postgraduate Medical Center, Karachi Pakistan, from Dec 2018 to Jun 2019. Methodology: Three hundred patients, aged 18-85 years of either gender were included in the study. Cases were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a case-control studies done in multiple countries where betel quid is a common habit, there were strong evidence of a higher risk of oral cancer in BQ chewers compared to non-chewers (Warnakulasuriya & Chen, 2022). A similar case-control study engaging 150 case and 150 control subjects at a military hospital in Pakistan showed that those who consumed betel were 2.28 times more likely to develop head and neck cancer as compared to people who did not consume betel and other products including tobacco ( (Nouman et al, 2022). A recent study confirmed high incidence of OSF in areas where habitual use of AN is prevalent (Senevirathna et al, 2023).…”
Section: Health Impacts Of Areca Nut Usementioning
confidence: 99%
“…In a case-control studies done in multiple countries where betel quid is a common habit, there were strong evidence of a higher risk of oral cancer in BQ chewers compared to non-chewers (Warnakulasuriya & Chen, 2022). A similar case-control study engaging 150 case and 150 control subjects at a military hospital in Pakistan showed that those who consumed betel were 2.28 times more likely to develop head and neck cancer as compared to people who did not consume betel and other products including tobacco ( (Nouman et al, 2022). A recent study confirmed high incidence of OSF in areas where habitual use of AN is prevalent (Senevirathna et al, 2023).…”
Section: Health Impacts Of Areca Nut Usementioning
confidence: 99%